Pengaruh Carbon Dots Dari Kulit Kentang Dengan Teknik Iradiasi Gelombang Mikro Terhadap Pertumbuhan Tanaman Cabai - Selvi Kurnia; Rahmat Firman Septiyanto; Yus Rama Denny M; Isriyanti Affifah (Pendidikan Fisika, FKIP, Universitas Nahdlatul Ulama Cirebon, 2025)
Carbon Dots (C-dots) are carbon-based nanomaterials that have fluorescent properties, are environmentally friendly, and are easily synthesized from organic waste materials. This research aims to synthesize C-dots from potato skins using the microwave irradiation method as an environmentally friendly and economical alternative to increase the growth of chili plants. Application tests on chili plants were carried out by adding C-dots solution to the growing medium in various concentrations (control, 50 mg/L, 60 mg/L, and 70 mg/L). Observation results showed that chili plants watered with C-Dots showed optimum growth rates found to occur with 50 mg/L carbon dots, compared to the control study, which shows a balance between growth stimulation and effective nutrient absorption without causing toxicity effects on the plants. Then, the resulting C-Dots samples were characterized using a UV-Vis Spectrophotometer using a wavelength range of 200-800 nm. The results of measurements with a UV-Vis spectrophotometer showed absorption at a wavelength of 251 nm and showed an absorbance peak of 4.379.